Willingness to Pay Carbon Offset Viewed from Individual, Organizational Factors and Public Perception of Carbon Offset: Study of Online Transportation Users in JABODETABEK - Indonesia - Soeharso, Silverius Y.; Yudi, Azis; Zulkifli, (International Journal of Scientific Research and Management (IJSRM), 2024)
To support the reduction of national CO2 levels, it is crucial to analyze the willingness to pay for carbon offsets as a consideration for carbon market policies in Indonesia. This study explores the willingness to pay for carbon offsets in the online transportation sector (Grab and Gojek) based on three factors (individual, organizational, and public). This study used a pragmatic sequential mixed method with 418 samples taken using a convenience sampling technique. The results are that pro-environmental behavior is a mediator variable between the individual and organizational levels on willingness to pay for carbon offsets. It is hoped that the results of this research can contribute to making policies related to carbon offset tariffs, which will technically be proposed by the Ministry of Environment and Forestry of the Republic of Indonesia, and the Indonesian Ministry of Finance will issue financial policies.